Factors Affecting the Occurrence of Stunting in Toddlers in Kalike Primary Health Center, South Solor Distric - Kukun, Angelus Fransiskus Watan; Ndoen, Honey; Purnawan, Sigit (Timorese Journal of Public Health, 2023)
Stunting is a long-term problem of malnutrition resulting in children who are too small for their age. Malnutrition occurs when the baby is in the womb and early after the baby is born, but stunting only appears after the baby is 2 years old. Data on stunting cases at the Kalike Health Center are 31.05% in 2020, 20.83% in 2021 and 17% for the August period in 2022. These statistics show that although the number of stunting cases around the Kalike Health Center has decreased, it is still far from the target of 14 percent set in the 2024 National Medium-Term Development Plan (RPJMN). toddlers in the Kalike Health Center area. The research used is a type of analytic observation research with a case control design. The sample in this study amounted to 78 respondents, consisting of 38 case samples and 39 control samples. The data collection instrument in this study used a questionnaire consisting of a questionnaire on maternal knowledge, food intake and parenting patterns. The sampling technique used is simple random sampling with matching. Data analysis used univariate and bivariate analysis with chi-square test. The results showed that the factors influencing stunting included mother's level of knowledge p=0.012 (OR=3.600), energy adequacy p=0.022 (OR=3.294), protein adequacy level p=0.041 (OR=2.875), and history of exclusive breastfeeding. p = 0.036 (OR = 3.035) and parenting style p = 0.038 (OR = 2.970), while factors that did not affect the incidence of stunting were parents' income p = 0.709 (OR = 0.567) and immunization status (p = 0.598). Education about the importance of exclusive breastfeeding must be increased and attention must be paid to a balanced diet, especially energy-sourced foods, to avoid growth retardation in toddlers.